Viability of R-290 Refrigerant as Residential AC Retrofit: Effect of Charge Mass Variations - Irham Aulia; Haftirman Haftirman; Ega Taqwali Berman (Universitas Mercu Buana, 2025)
The growing concerns over ozone depletion and global warming caused by refrigerants have led to the search for environmentally friendly alternatives. This study evaluates the impact of varying R-290 refrigerant charge masses on the performance of a wall-mounted residential air conditioner using the drop-in substitute method. A ¾ HP residential AC unit originally charged with 550 grams of R-22 refrigerant was retrofitted with R-290 and tested at charge masses of 140 grams, 165 grams, and 190 grams—approximately 25%, 30%, and 35% of the original R-22 charge, in accordance with the commonly applied “one-third rule.” The results showed that retrofitting with R-290 increased the Refrigeration Effect (RE) by up to 75%, Compression Work (Wc) by 68%, and Coefficient of Performance (COP) by up to 18%. The system with a 25% refrigerant charge was unable to reach the set temperature due to a 23% reduction in cooling capacity, while the 30% charge showed a 10% reduction. The 35% refrigerant mass retrofit proved the most suitable, achieving adequate cooling capacity, an 18% increase in COP, and a 14% reduction in power consumption. Additionally, the retrofit resulted in an indirect CO₂ emission reduction of 1.15 metric tons annually, highlighting the environmental and energy-saving advantages of using R-290. These findings provide empirical validation of the one-third rule for refrigerant mass variation in R-290 retrofits and offer valuable insights into optimizing performance and efficiency in residential AC units, with significant energy and environmental benefits.